Comparıson Of Dıfferent Cephalometrıc Measurements In Dıagnosıs Of Vertıcal Growth Pattern - Nazan Küçükkeleş; Sibel Biren (Galenos Yayinevi, 1996)
Pretreatment lateral cephalometric radiographs of 120 patient s having criteria commonly used for identifying patients with low angle growth pattern were traced and measured. Results indicate that different parameters identify different patients. Association ratios of total angle, gonial angle, and Jarabac ratio with overbite were found higher comparatively. Patients identified as low angle by commonly used parameters like, mandibular plane angle and lower anterior face height/total anterior face height ratio were identified different by other parameters. Values of FMA and Y angles were not harmonious with other parameters, but the patients selected with these criteria (FMA&Y angle) identified similar by other parameters.